Zirconia/carbon nanotube aerogel hybrid material: electrophysical and chemisorbtion properties - Tolmacheva, E.A.; Morozov, I.A.; Starostin, A.G. (Perm Federal Research Centre Journal, 2017)
The work is devoted to investigation of electrophysical properties of a zirconia/carbon nanotube composite and analysis of its sorption ability in relation to hydrogen. On the basis of conductive atomic-force microscopy, as well as the experiments performed on macroscopic scale it has been revealed that the material exhibits bulk percolation cluster-like conductivity. Besides, the synthesized material actively sorbs hydrogen in constant flow mode, as well as with a pulsed gas supply. The discovered properties of the composite make it of high demand in the field of catalysis, water vapor sensors and etc.